Pengaruh Meronce Terhadap Kecerdasan Logika Matematika Anak Kelompok A Di Ra Ip Qurrota A'yun Ngrandu Nglorog Sragen Tahun Ajaran 2016/2017 - Mustika Asri, Ariyani, DR Darsinah M.Si (2017)
The purpose of this research is to know determine the effect on intelligence meronce mathematical logic A group of children in the IP RA Qurrota A'yun Ngrandu Nglorog Sragen Academic Year 2016/2017. This research is experimental research design One-Group Pretest-Posttest design.Subjek this research is the students group A in RA IP Qurrota A'yun Ngrandu Nglorog Sragen Academic Year 2016 / 2017. Data child intelligence gathered through observation and dokumentation.Data analysis technique used is the t-test. The results of the data analysis the value tcount-23,311 ≤ ttable1,753then Ho denied and Ha is received. Thus it can be concluded that the meronce effect the mathematical logic of children's Group A RA IP Qurrota A'yun Ngrandu Nglorog Sragen academic year 2016/2017.